Relationship between first pass effect NLR and PLR in mechanical thrombectomy for acute anterior circulation large-vessel occlusion - Lu, Guozhang; Wang, Peijian; Xv, Bin; Lv, Hang; Zhang, Liyong; Wang, Jiyue; Hao, Jiheng (Frontiers in Neurology, 2025)
PurposeThe study investigated the correlation between the neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) concerning the first-pass effect (FPE) observed during mechanical thrombectomy subsequent to acute ischemic stroke (AIS).MethodsPatients diagnosed with AIS in the anterior circulation, who underwent mechanical thrombectomy between January 2020 and December 2022, were assessed. Various data were collected, including blood cell counts, general information, relevant surgical and clinical details, and functional outcomes determined by the Modified Rankin Scale (MRS) score ≤2 at 3 months. Logistic regression was utilized to identify independent factors predicting the first-pass effect (FPE) and to explore the associations between FPE and the NLR and PLR. Critical NLR and PLR values were examined using Receiver-operating characteristics (ROC) curves.ResultsA total of 233 patients were enrolled and categorized into either the FPE or MPE groups based on the success of the initial thrombectomy. The FPE group showed significant distinctions compared to the MPE group in both NLR and PLR levels: NLR (3.63 vs. 4.90, p < 0.001), PLR (134.92 vs. 164.77, p = 0.001). Both univariate and multivariate regression analyses demonstrated the independent predictive ability of NLR and PLR for assessing the risk of FPE during mechanical thrombectomy, with NLR (Adjusted Odds ratio (OR) 0.764; 95% CI 0.665–0.878, p = 0.001) and PLR (Adjusted OR0.993; 95% CI 0.989–0.998, p = 0.002). Moreover, the ROC curves delineated critical threshold values of 4.34 and 148.03 for NLR and PLR, respectively.ConclusionThe increase of NLR and PLR may be related to the failure of FPE.